Fluorinated Protein and Peptide Materials for Biomedical Applications - Julia M. Monkovic; Halle Gibson; Jonathan W. Sun; Jin Kim Montclare (MDPI AG, 2022)
Fluorination represents one of the most powerful modern design strategies to impart biomacromolecules with unique functionality, empowering them for widespread application in the biomedical realm. However, the properties of fluorinated protein materials remain unpredictable due to the heavy context-dependency of the surrounding atoms influenced by fluorine's strong electron-withdrawing tendencies. This review aims to discern patterns and elucidate design principles governing the biochemical synthesis and rational installation of fluorine into protein and peptide sequences for diverse biomedical applications. Several case studies are presented to deconvolute the overgeneralized fluorous stabilization effect and critically examine the duplicitous nature of the resultant enhanced chemical and thermostability as it applies to use as biomimetic therapeutics, drug delivery vehicles, and bioimaging modalities.